Implementasi dan Optimalisasi Voice Order Internet Protocol (VOIP) Menggunakan NDLC Untuk Komunikasi Antar Lantai - Ruhul Khomar; Arif Harbani (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2021)
VoIP as an internet service is commonly called ip telephone. Internet infrastructure is needed in order to use or provide VoIP services. Some offices use local communication to communicate within the office environment itself, but cannot connect to other offices because it is only a local phone. This research aims to implement the Voice Over Internet Protocol (VoIP) by utilizing wireles local area network (WLAN) facilities by building a VoIP server. The development model used in this research is a user interface that is built alone to be applied on Android phones. This user interface is as a face-to-face tool for fellow VoIP users. The study was conducted at the West Bogor sub-district office with 23 respondents as a sample of application trial subjects. The results of the analysis showed 78.66% of the application eligibility level, showing the application or system made was considered good.